lac Up-promoter mutants with increased homology to the consensus promoter sequence. - Mandecki, W (1985)
Four lac promoter mutants were constructed. The mutations increased the homology between the lac promoter and the consensus promoter sequences by introducing the consensus -10 and -35 regions and the consensus spacing of 17 residues between these two regions. The promoter mutants were cloned into a pBR322-derivatized vector upstream from the lacZ gene, and levels of beta-galactosidase were an indication of promoter activity. All mutants exhibited higher activity than did the wild-type promoter.